The Brazil northeast experience (London : International Video Network, 1995)
Dance to the rhythm of Brazil's hottest percussion group ... play a game of soccer on the beach ... float down the Amazon during a rainstorm ... scale a palm tree ... try your hands at capoiera - a martial arts and acrobatics ... experience Brazil
Copy available in DVD format
Title from data sheet
Keywords: Brazil -- Description and travel